An explanatory model of the organizational factors that explain the adoption of e-business - Marta Beatriz García-Moreno; Susana García-Moreno; Juan Jose Nájera-Sánchez; Carmen de Pablos Heredero (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: to describe the factors that facilitate the adoption of e-business in firms. To go in deep on the factors, resources and capabilities that need to be present in those firms seeking to improve their levels of e-business adoption. Design/methodology/approach: analysis of the literature involving the main theories on business administration, and more specifically, on those related to technology innovation (TI) and information systems (IS), as applicable to the organizational factors that explain the adoption of e-business. Findings: it identifies three main sources of influence: a first group covers the characteristics of the actual firm, which refer to the organisation's specific features: firm size, the backing of top management, expected benefit, age, the level of human capital, and international projection. A second group of factors includes technology-related characteristics. The third group contains all those aspects in the environment that may affect the firm's attitude to e-business. Research limitations/implications: the chosen variables play significant role following a review of the studies on the subject, but not all potential ones have been included. The variables have been chosen in view of the large number of studies that have reported conclusive results. Practical implications: the model presented is designed to enable both scholars in this field and decision-makers in strategic matters to reflect upon those aspects that may drive the adoption of e-business, and thereby help them to make more informed decisions on the matter. Social implications: In highly competitive industries, firms need to keep themselves permanently up to speed with technological advances and strategic innovations. Originality/value: it is the first study that considers three different perspectives: the organizational, the technological and the environmental one.
Keywords: 650; e-business; adoption of e-business; technology; organisation; environment